Development of a nurse-led clinical pathway to prevent delirium in older adults in general hospital wards: a realist review protocol - Hoch, Jonas; Müller, Martin; Unger, Inga; Mitzkat, Anika; Denninger, Natascha-Elisabeth (BMJ open, 2025)
Introduction Delirium is a critical and complex neuropsychiatric syndrome that significantly affects older adults in general hospital wards. Although multicomponent interventions have been shown to be effective in preventing delirium, the consistent implementation remains a challenge. Also, to manage the complex pathway of patients from admission to discharge in hospital, the involvement of the nursing staff is essential. Developing a nurse-led clinical pathway for delirium prevention could provide a structured approach to improving care quality. For intervention development taking account of the complexity of the clinical environment, the UK Medical Research Council framework is frequently used. A core element of this framework is mapping a programme theory that explains how, for whom and in what circumstances an intervention may work. The realist review methodology is well suited to uncovering the underlying mechanisms, contexts and outcomes of interventions, translating these into a programme theory.The aim of this realist review is to develop a programme theory for a nurse-led clinical pathway to prevent delirium in older adults aged 65 years or older in general hospital wards and to identify strategies to support its effective implementation. - Methods and analysis The realist review is based on the methodical framework developed by Pawson et al and further adapted by Rycroft-Malone et al and the reporting will follow the Realist And MEta-narrative Evidence Syntheses: Evolving Standards guidelines. The process comprises four steps: (1) defining the review scope; (2) systematically searching for and appraising the evidence; (3) extracting and synthesising findings and (4) developing a narrative synthesis. Interest holders, including clinical and academic experts, will be actively involved as an expert reference group to inform and refine the programme theory. The final programme theory will be presented in Context-Mechanism-Outcome configurations and the Implementation Research Logic Model. - Ethics and dissemination Since no data are collected as part of the review, ethical approval is not required. Findings will be disseminated through academic conferences and publication in a peer-reviewed journal. - Registration This protocol has been registered at Open Science Framework (https://doi.org/10.17605/OSF.IO/7EPTF).